Potensi Wirausaha Pertanian Pada Masyarakat Desa PenyanggaTaman Nasional Meru Betiri - Mochamad ilham Firdaus; Luh Putu Suciati (UNEJ e-Proceeding, 2018)
This study aims to determine the potential of agricultural entrepreneurs in the Wonoasri Village community as a buffer village of Meru Betiri National Park. The study was conducted in Wonoasri Village, Tempurejo Subdistrict, Jember Regency with the consideration that Wonoasri Village has village potential in the form of non-timber forest products or ecotourism objects. The research method used is descriptive-analytic method. The method of data collection is done by interviewing using questionnaires, observation and documentation. Respondents in this study were 30 people and 3 expert respondents or experts (those who were considered to have the ability to understand the related problems). Data analysis uses a scoring analysis of the potential of agricultural entrepreneurs in rural communities. The results showed the level of agricultural entrepreneurial potential in the Wonoasri Village community as a whole obtained a value of 83.28, which means included in the high category. In the seven indicators there are several differences in the assessment of each indicator, where innovative and proactive indicators fall into the adequate category, then five other indicators fall into the high category of risk taking, results orientation, commitment with various parties, confidence, and leadership, while business management indicators fall into a very high category. The Wonoasri villagers already have a joint business group (KUBE) that supports the efforts made by the village community. In addition to KUBE, there are shops or other service businesses with a total of 87 shops in the Wonoasri Village area which reinforce the results of research that the level of potential of agricultural entrepreneurs in the Wonoasri Village community is high.